2013
DOI: 10.1021/cg3013156
|View full text |Cite
|
Sign up to set email alerts
|

High Yield Bi2Te3 Single Crystal Nanosheets with Uniform Morphology via a Solvothermal Synthesis

Abstract: Hexagonal nanosheet of Bi 2 Te 3 single crystals with uniform morphology were facilely synthesized through a high yield solvothermal route at low temperature (180 °C). Xray diffraction, scanning electron microscope, transmission electron microscope, selected area electron diffraction, and high-resolution transmission electron microscope were employed to characterize the products. In this solvothermal process, ethylene glycol (EG) was used as both reducing agent and solvent to simplify the process. The reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 34 publications
3
87
0
Order By: Relevance
“…Bi 2 Te 3 nanoplates usually contain a single-crystalline phase, with the typical diameter on the order of submicrons and thickness of approximately 30 nm. [15][16][17] The electrical and thermal transports along the top-bottom crystallite plane are quite different from those along the c-axis direction, which is perpendicular to these top-bottom planes. In addition, it has been recently reported that ultrathin nanoplates of Bi 2 Te 3 and related alloys exhibit the characteristics of topological insulators.…”
Section: Introductionmentioning
confidence: 99%
“…Bi 2 Te 3 nanoplates usually contain a single-crystalline phase, with the typical diameter on the order of submicrons and thickness of approximately 30 nm. [15][16][17] The electrical and thermal transports along the top-bottom crystallite plane are quite different from those along the c-axis direction, which is perpendicular to these top-bottom planes. In addition, it has been recently reported that ultrathin nanoplates of Bi 2 Te 3 and related alloys exhibit the characteristics of topological insulators.…”
Section: Introductionmentioning
confidence: 99%
“…12 Especially, rhombohedral structured Bi 2 Te 3 nanoplates, as twodimensional nanostructures, [13][14][15] exhibit strengthened phonon scattering due to the dense grain boundaries after sintered into pellets. 16 To further strengthen the phonon scattering, we can assemble the randomly orientated nanoplates in the form of well-aligned hierarchical nanostructures.…”
mentioning
confidence: 99%
“…2(e). Syntheses of disk-like Bi 2 Te 3 NPs with diameters ranging from approximately 10 nm-2.0 lm by various synthesis methods were widely reported [14,18,[21][22][23][24][25][26][27][28]. A rhombohedral Bi 2 Te 3 crystal has a layered anisotropic lattice structure with the Te and Bi atom layers arranged in the order of -Te (1) -Bi-Te (2) -Bi-Te (1) -along the c-axis direction [10].…”
Section: Synthesis Of Bi 2 Te 3 Npsmentioning
confidence: 99%